A novel domino reaction for the preparation of substituted non-racemic β-proline derivatives. Issue 40 (6th October 2016) - Gilbert, Eric J.; Brunskill, Andrew; Cai, Jiaqiang; Cai, Yaxian; Chu, Xin-Jie; Dai, Xing; Hao, Jinsong; Kuethe, Jeffrey T.; Lai, Zhong; Liu, Hong; Mu, Cuizhi; Qi, Yan; et al.
Abstract: A novel domino reaction for the preparation of non-racemic β-proline derivatives is reported. The addition of a methyl 2-(oxetan-3-yl)acetate titanium enolate to chiral tert -butanesulfinyl ketimines followed by an intramolecular oxetane ring-opening provides the highly-substituted pyrrolidine ring systems with three contiguous stereogenic centers. Graphical abstract: